Increased NO bioavailability in aging male rats by genistein and exercise training: using 4, 5-diaminofluorescein diacetate - Siriviriyakul Prasong; Suksom Daroonwan; Eksakulkla Sukanya; Patumraj Suthiluk (BMC, 2009)
Abstract Background Several kinds of anti-oxidants have drawn a lot of intension for their benefits on vascular protection. In addition, it has been demonstrated that exercise training could improve endothelial function by up-regulating endothelial nitric oxide synthase (eNOS) protein. Therefore, the present study aims to investigate the effects of genistein, a potent phyto-antioxidant, and exercise training on age-induced endothelial dysfunction in relation to NO bioavailability using in situ NO-sensitive fluorescent dye detection. Methods Male Wistar rats (20-22-month old) were divided into four groups: aged rats treated with corn oil, (Aged+Veh, n = 5), aged rats treated with genistein (Aged+Gen, n = 5, (0.25 mg/kg BW/day, s.c.)), aged rats with and without exercise training (Aged+Ex, n = 5, swimming 40 min/day, 5 days/week for 8 weeks) (Aged+Without-Ex, n = 5). Cremaster arterioles (15-35 micrometer) were visualized by fluorescein isothiocyanate labeled dextran (5 microgram/ml). The vascular response to acetylcholine (Ach; 10-5M, 5 ml/5 min) was accessed after 1-min norepinephrine preconstriction (10 micro molar). To determine NO bioavailability, the Krebs-Ringer buffer with 4, 5-diaminofluorescein-diacetate (3 micro molar DAF-2DA), and 10 micro- molar Ach saturated with 95%N2 and 5%CO2 were used. Changes of DAF-2T-intensities along the cremaster arterioles were analyzed by the Image Pro-Plus Software (Media Cybernatics, Inc, USA). Liver malondialdehyde (MDA) level was measured by thiobarbituric acid reaction and used as an indicator for oxidative stress. Results The results showed that means arterial blood pressure for both Aged+Gen and Aged+Ex groups were significantly reduced when compared to the Aged groups, Aged+Veh and Aged+Without-Ex (P < 0.05). Among the treated groups, Ach-induced vasodilatation were significantly increased (P < 0.05) and was associated with increased NO-associated fluorescent intensities (P < 0.05). On the other hand, MDA levels were significantly reduced (P < 0.05) when Aged+Veh was compared to Aged+Without-Ex. Conclusion These findings showed that genistein and exercise training could improve age-induced endothelial dysfunction and is related to the increased NO bioavailability.